Analisis Keberlanjutan Usaha Padi Sawah Di Kecamatan Purwodadi Kabupaten Musi Rawas Provinsi Sumatera Selatan - ZA, Sisma; Santoso, Urip; Brata, Bieng; Yurike, Yurike; Suharyanto, Suharyanto (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
The decline in rice production can pose a risk to Indonesia's food sovereignty. To ensure the sustainability of agriculture in general and food supply in particular, the concept of sustainable development needs to be implemented. Purwodadi District, which is one of the rice production centers in Musi Rawas Regency, has an advantage because all of its rice fields are irrigated by an irrigation system. Currently, many farmers who previously planted rice have switched to fish farming and building swallow's nests, which has resulted in a narrowing of the area of ​​rice fields. This study aims to analyze the sustainability status and sensitive attributes in rice farming efforts in Purwodadi District, Musi Rawas Regency, South Sumatra Province. The research method used was an interview with a questionnaire which was then analyzed using the Multidimensional Scaling method. The results of the study showed that the sustainability status of rice farming efforts in Mardiharjo Village, Purwodadi District, had a sustainability index of 60.21, which can be categorized as quite sustainable. A total of 16 sensitive attributes have been identified as significant factors and influence the sustainability of rice farming efforts